Incidence of skeletal related events in patients with bone metastasis receiving denosumab every four weeks compared to intervals greater than every four weeks. (April 2019) - Yerram, Prakirthi; Moore, Russell; Wolf, Steven; Barbour, Sally Y
Objective: Denosumab is a monoclonal antibody used for prevention of skeletal related events in patients with bone metastasis from solid tumors and is administered every four weeks. In our practice, denosumab is often given at different frequencies more similar to patient's chemotherapy regimens to decrease frequency of clinic visits. The purpose of this study is to compare the incidence of skeletal related events, incidence of hypocalcemia, and cost with denosumab given at every four weeks and denosumab given at other frequencies. Methods: This retrospective study at Duke University Health System included solid tumor patients with an age ≥18 years who received denosumab for prevention of skeletal related events. Results: A total of 94 patients were included, with 29 in the every four-week group and 65 in the greater than every four-week group. Patients who received denosumab every four weeks had a 41.4% incidence of skeletal related events compared to 26.2% incidence of skeletal related events in patients who received denosumab at intervals greater than every four weeks (OR: 0.50; p = 0.14). There was no statistically significant difference in incidence of hypocalcemia. Based on average wholesale price, when the frequency of denosumab is extended to greater than every four weeks, annual cost savings per patient ranged from $4700 (every 5 weeks) to $18, 800 (every 12 weeks). Conclusion: While this study raises the possibility of decreasing the frequency of denosumab administration, further data are necessary to confirm that less frequent administration is non-inferior to every four-week administration.